FENOMENA KESULITAN MEMBACA PADA SISWA KELAS II SEKOLAH DASAR (STUDI KASUS DI SDN PATI KIDUL 01) - Umi Nareswari Baroroh; M. Arsyad Fardani; Lintang Kironoratri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The purpose of this study was to describe the form of reading difficulties of class II students at SD Negeri Pati Kidul 01. This type of research is a qualitative research with a case study approach. Sources of data in this study were class II teachers, as well as 4 grade II students who had difficulty reading at the beginning. Data collection techniques used are interviews, observation, and documentation. The data analysis technique uses the Milles and Huberman model with stages, data reduction, data presentation, and drawing conclusions. The results showed that there were still some students who had difficulty reading beginning in grade II at SDN Pati Kidul 01. The reading difficulties experienced by students were (1) difficulty spelling, (2) difficulty distinguishing letters that were almost the same shape, (3) difficulty paying attention to signs reading, (4) Errors in replacing letters or syllables, (5) Errors in identifying sentences that contain combinations of consonants and combinations of diphthongs, (6) Difficulties in understanding a story